Early Sources of Children's Math Achievement in Chile: The Role of Parental Beliefs and Feelings about Math. Issue 5 (4th July 2021) - del Río, M. Francisca; Susperreguy, María Inés; Strasser, Katherine; Cvencek, Dario; Iturra, Carolina; Gallardo, Ismael; Meltzoff, Andrew N.
ABSTRACT: Research Findings : Two hundred and sixty-seven Chilean children from grades 1–3, their fathers and their mothers completed measures of implicit and explicit math-related beliefs (math–gender stereotypes, math self-concepts) and feelings (math anxiety), as well as tests of mathematical achievement. Children, fathers, and mothers exhibited stereotypes that link math with males. More specifically, mothers identified more with language than with math, while fathers and children identified more with math than with language. Path analyses models revealed that children's explicit math self-concepts significantly predicted their actual math achievement. Children's explicit self-concept was, in turn, explained marginally by the mathematical anxiety of their mothers. Practice or Policy : These results contribute to our understanding of the relation between parental and children's beliefs and children's math achievement during early elementary school years. In countries such as Chile, with a significant gender gap in math achievement, these findings may highlight relevant aspects to consider when designing interventions aimed at educational equity and providing equal mathematical learning opportunities to boys and girls.